2007
DOI: 10.1017/s1041610207006035
|View full text |Cite
|
Sign up to set email alerts
|

Time that tells: critical clock-drawing errors for dementia screening

Abstract: Background-Clock-drawing tests are popular components of dementia screens but no single scoring system has been universally accepted. We sought to identify an optimal subset of clock errors for dementia screening and compare them with three other systems representative of the existing wide variations in approach (Shulman, Mendez, Wolf-Klein), as well as with the CDT system used in the Mini-Cog, which combines clock drawing with delayed recall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 31 publications
2
55
0
1
Order By: Relevance
“…Cognitive status was determined by use of the Mini-Cog test 17 and a clockdrawing test. 18 The clock-drawing component of the test provided a quick assessment of cognitive function, memory, language comprehension, visual-motor skills, and executive function and thus screened out patients with dementia or mild cognitive impairment. 18 Patients with a word recall score of 0 (range, 1-3) or a word recall of ≤2 with an abnormal clock drawing were excluded.…”
Section: Methods Trial Design and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cognitive status was determined by use of the Mini-Cog test 17 and a clockdrawing test. 18 The clock-drawing component of the test provided a quick assessment of cognitive function, memory, language comprehension, visual-motor skills, and executive function and thus screened out patients with dementia or mild cognitive impairment. 18 Patients with a word recall score of 0 (range, 1-3) or a word recall of ≤2 with an abnormal clock drawing were excluded.…”
Section: Methods Trial Design and Participantsmentioning
confidence: 99%
“…18 The clock-drawing component of the test provided a quick assessment of cognitive function, memory, language comprehension, visual-motor skills, and executive function and thus screened out patients with dementia or mild cognitive impairment. 18 Patients with a word recall score of 0 (range, 1-3) or a word recall of ≤2 with an abnormal clock drawing were excluded. 17,18 Reading difficulty secondary to eyesight problems was not a cause for exclusion, and large-print questionnaires and diaries and digital scales with large numbers were available to all enrolled patients.…”
Section: Methods Trial Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors suggested that qualitative analysis of errors in clock drawing might improve diagnostic accuracy for dementia screening. For instance, errors such as inaccurate time setting, missing hands or numbers, and number substitutions or repetitions might be particularly useful for dementia screening [63]. Using appropriate error classification criteria, error analysis in CDT might be useful to differentiate different types of dementia, since conceptual errors are quite frequent in AD [64], but in a recent longitudinal study conceptual errors and perseverations were more frequently observed in the advanced stages of all dementing diseases, whereas spatial and planning errors were more frequent in mild-tomoderate dementia [65].…”
Section: Drawing Tasks Frequently Used In Dementiamentioning
confidence: 99%
“…Analogously, in a further brain morphometric study on MCI and AD patients, accuracy in copying the ROCF was significantly different in MCI patients, AD patients, and healthy controls [87]. It has also been observed that MCI patients make conceptual and graphic errors more often than matched healthy controls, and that AD patients score lower and make significantly more conceptual, graphic, and spatial-planning mistakes than MCI individuals, thus suggesting that a detailed scoring system is necessary to differentiate individuals with MCI from healthy adults [63,93]. Scoring systems focusing on hand and number placement might better differentiate MCI individuals from healthy controls, but the solidity of CDT as a screening tool for MCI has been questioned [94].…”
Section: Drawing Disorders In Prodromic (Amci) and Clinical Forms Of Admentioning
confidence: 99%